Data collection using unmanned aerial vehicles for Internet of Things platforms. (May 2019) - Goudarzi, Shidrokh; Kama, Nazri; Anisi, Mohammad Hossein; Zeadally, Sherali; Mumtaz, Shahid
Abstract: In many of the Internet of Things (IoT) applications, a network of sensors that are wirelessly connected is vital because it provides a better picture of remotely sensed environments. However, traditional network data collection consumes a high amount of energy because of data packets that need to be routed on a hop-by-hop basis to the base station. To alleviate this problem, Unmanned Aerial Vehicles (UAV) have been used to travel over the sensed environment to collect data. The time and motion constraints of UAVs mean that they require the shortest and smoothest paths to address these constraints. So, the shortest path is planned based on Travelling Sales Problem (TSP), and to smoothen the path, we used Bezier curves to convert paths that are flyable. The proposed algorithm exhibits faster data collection in comparison with other solutions, while achieving a high delivery rate of packets and a low energy usage.